Energi Listrik pada Industri Kecil Teh Celup Herbal Daun Urokep - Deby Mipa Salam; Andrian Fernandes; Rizki Maharani (Proklamasi 45 University, 2022)
Urokep leaf or Chinese Ketepeng (Senna alata) is one of the most commonly found medicinal plants and can be used as raw material for herbal tea bags. An essential process in making herbal tea on a household scale is the chopping of dried leaves into a powder that is ready to be put into teabags and pressing the teabags. The leaf shredder process can use a chopper and a blender, while the teabag pressing process uses an impulse sealer. This study aims to compare the energy needed by choppers and blenders in making urokep leaf teabag powder, as well as the use of impulse sealers with element lengths of 20 cm and 30 cm. The research was divided into two stages, i.e. chopping the dried leaves into the powder stage and pressing the teabags stage. The chopping dry leaf into the powder stage was counted by calculating the time for the chopper and blender to powder 1 kg of dry leaves. The pressing of the teabags was carried out by calculating the pressing time of 1000 teabags using an impulse sealer with 20 cm and 30 cm element length. The amount of electrical energy is used by multiplying the electric power by the time of each tool.The results showed that the electrical energy used by the chopper to shredder 1 kg of dry Urokep leaves was 0.10833 KwH, while the blender required more energy, which was 0.27833 KwH. The electrical energy to press 1000 teabags used by the impulse sealer 20 cm is lower at 0.310 KwH than the impulse sealer 30 cm 0.633 KwH. The combination of a chopper and impulse sealer 20 cm is highly recommended for household-scale industries.